__
__1. Graph the functions, f (x) = x^{3} +1, g (x) = x^{3} - 5, h (x) = (- x)^{3} + 4. Compare these graphs to their toolkit function, k (x) = x^{3}. Describe the transformations on k (x) that would result in f, g and h.

2. Graph the functions, f (x) = (x + 1) ^{3} , g (x) = - (x - 5)^{3} , h (x) = (x + 4)^{3} . Compare these graphs to their toolkit function, k (x) = x^{3}. Describe the transformations on k (x) that would result in f, g and h.

3. Graph the functions, f (x) = abs (x) + 5, g (x) = 1/ (x + 2), h (x) = - abs(x + 3) - 3. Compare these graphs to their toolkit functions, k (x). Describe the transformations on k(x) that would result in f, g and h.

4. If k (x) = x write the transformations required to obtain f(x) = 0.5 abs(x - 1) - 4

For 5 - 9, if k (x) = 3x - 2 write the expression for g (x) if the graph of g is obtained by:

5. A reflection across the y axis 6. A reflection across the x axis

7. A vertical translation of +3 units 8. A horizontal translation of - 3 units

9. A vertical stretch of 3 units

10. For the graph of k (x) below, sketch the graph that corresponds to the following transformations: